Formation of Polydiacetylene/Silica Nanocomposite as a Colorimetric Indicator: Effect of Time and Temperature. Issue 1 (25th September 2012) - Nopwinyuwong, A.; Boonsupthip, W.; Pechyen, C.; Suppakul, P.
Abstract This work presents a method to prepare a new class of polydiacetylene (PDA)/SiO2 nanocomposites for colorimetric indicator applications. The silica concentration is 5 wt% of the diacetylene monomer, 10, 12‐pentacosadiynoic acid (PCDA). Under ultraviolet light irradiation, PCDA vesicle/silica nanocomposites were formed and an intense blue solution was obtained. The silica nanoparticles can improve chromic properties of molecules. The color transition of PDA/silica nanocomposites can change from blue (λmax∼ 640 nm) to red (λmax∼ 540 nm), which is irreversible when stored at different temperatures and time. This study investigated characterization of the aqueous suspension compared with pure PDA vesicles in the absorption spectra. Moreover, the color response was calculated. This is an efficient method for preparation of the colorimetric sensor of nanocomposite materials after UV irradiation. The PDA/5 wt% silica nanocomposites aqueous matrix would potentially be developed as a new colorimetric polymeric indicator to study the effect of temperature and time. © 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E724–E731, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21315